What animals want : expertise and advocacy in laboratory animal welfare policy - Carbone, Larry (Oxford University Press, 2004)
Larry Carbone provides a balanced and reasonable advocacy of animal rights, looking at how to ethically and responsibly conduct biomedical and behavioural research that respects the rights and welfare of all subjects including animals.